Media Pembelajaran Berbasis E-Learning dalam Meningkatkan Pemahaman Pembelajaran Pendidikan Agama Kristen di Era Digital - Raja Holong Simatupang; Yeti Merianti Boimau; Owen Petrus Gultom (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Advances in digital technology are driving the transformation of Christian Religious Education towards a more flexible and interactive e-learning system. The implementation of e-learning still faces limitations in terms of teacher competence and digital infrastructure. These conditions highlight the need to strengthen digital pedagogy so that Christian Religious Education remains relevant, contextual and transformative in the modern era. This study aims to analyse the role of e-learning in enhancing students’ understanding of Christian Religious Education in the modern digital era. The research employs a descriptive qualitative approach through a literature review with interpretative analysis of various Christian Religious Education texts. The findings indicate that e-learning can enhance understanding of faith through interactive, flexible learning and creative digital media. Further findings indicate that strengthening teachers’ digital competencies is crucial to the effectiveness of transformative e-learning-based Christian Religious Education. Christian Religious Education e-learning needs to be developed through an interactive pedagogical approach. Furthermore, the development of digital platforms grounded in Christian values can create learning that is contextual, adaptive, and relevant to the modern digital generation. Abstrak Perkembangan teknologi digital mendorong transformasi pembelajaran Pendidikan Agama Kristen menuju sistem e-learning yang lebih fleksibel dan interaktif. Implementasi e-learning masih menghadapi keterbatasan kompetensi guru, infrastruktur digital. Kondisi tersebut menunjukkan perlunya penguatan pedagogi digital agar pembelajaran Pendidikan Agama Kristen tetap relevan, kontekstual, dan transformatif di era modern. Penelitian ini bertujuan menganalisis peran e-learning dalam meningkatkan pemahaman Pendidikan Agama Kristen peserta didik era digital modern. Penelitian menggunakan pendekatan kualitatif deskriptif melalui studi pustaka dengan analisis interpretatif terhadap berbagai literatur Pendidikan Agama Kristen. Hasil penelitian menunjukkan e-learning mampu meningkatkan pemahaman iman melalui pembelajaran interaktif, fleksibel, dan berbasis media digital kreatif. Hasil lainnya menunjukkan penguatan kompetensi digital guru sangat menentukan efektivitas pembelajaran Pendidikan Agama Kristen berbasis e-learning transformatif. E-learning Pendidikan Agama Kristen perlu dikembangkan melalui pendekatan pedagogi interaktif. Dan pengembangan platform digital berbasis nilai Kristen mampu menciptakan pembelajaran yang kontekstual, adaptif, dan relevan bagi generasi digital modern.